A Study on Corporate Governance Practices of Selected Banks in India - Sandhya, S.; Parashar, Neha (Indian Journal of Finance, 2019)
With the ever increasing complexity in the financial markets, the concept of corporate governance is carving a niche for itself. Off late, corporate governance has gained increasing attention from regulatory authorities and investors. Consistently over the past few years, regulatory changes have been made for governance practices in India and all over the world. Corporate governance ratings are being published for the ease of investment decisions, and corporate governance indexes are prepared by regulatory & non - regulatory agencies and researchers. In the present study, a corporate governance index for banks in India comprising of six sub - indexes was prepared and a comparison of selected public and private sector banks was done. Using the values of the index, the relation between corporate governance and banks' performance was ascertained using regression. It was found that corporate governance scores for private banks were greater than that of public sector banks, and when comparing the sub - indexes, private sector banks scored more in all of them, except risk management. A weak positive correlation was found between corporate governance and financial performance measured as ROA and NIM, and a significant correlation was found between corporate governance and PBV ratio.